NEUROKARDIOLOGI: INTERAKSI JANTUNG DAN OTAK - Sidhi Laksono (Universitas Ciputra Surabaya, 2022)
The heart-and-brain axis is an important connection and is known as neurocardiology. This science combines the specialization of cardiology and neurology in dealing with cases of nervous and cardiovascular systems. Any dysfunction in one of the components will interfere with that of the other component. Abnormalities of the nervous system can result in different changes in the cardiovascular function and structure, ranging from temporary changes in the ECG to myocardial injury, cardiomyopathy, and even cardiac death. This article reviews the anatomy and physiology of the central nervous system (CNS) and autonomic nervous system (ANS) in relation to the control of cardiovascular function in physiological and pathological states. In conclusion, the interaction between the heart and the brain affects one another, therefore, any abnormalities in the brain may cause abnormalities in the heart. It is hoped that knowledge of the heart and brain axis can provide an overview of knowledge about heart abnormalities caused by neurological disorders.